Cloning and Characterization of Cholesterol 25-Hydroxylase (ch25h) From a Marine Teleost, Chinese Tongue Sole (Cynoglossus semilaevis), and Its Gene Expressions in Response to Dietary Arachidonic Acid - Xu, Houguo; Sun, Bo; Jia, Linlin; Wei, Yuliang; Liao, Zhangbin; Liang, Mengqing (Frontiers in Marine Science, 2020)
Our previous studies have shown that ARA regulated the gonadal steroidogenesis and the synthesis of gonadotrophin-releasing hormone (GnRH) in the brain in a gender-dependent manner in Chinese tongue sole, a marine teleost with typical sex dimorphism. As a following up-study, the current study aimed to clone and characterize a gene responding to dietary ARA differently between males and females, cholesterol 25-hydroxylase (ch25h), which has important roles in cholesterol and lipid metabolism of mammals, but is rarely investigated in fish. The full-length cDNA of Chinese tongue sole ch25h was cloned and characterized, and its transcription in the gonads, brain and liver of both males and females in response to dietary ARA levels (0.34%, 2.53%, and 9.63% of TFA) was investigated. The Chinese tongue sole Ch25h, which putatively is Ch25h subtype B, shared moderate identity to its known orthologs of other teleost and lower identity to human Ch25h. It has high transcription levels in the gonads, followed by skin and muscle, but low levels in the intestine, spleen, and kidney. High ARA levels significantly increased the ch25h transcription in the gonads and brain of male fish, but did not affect the transcription in the females. However, the effect of dietary ARA on ch25h transcription in the liver showed an opposite gender-difference pattern to those in the gonads and brain. To our knowledge, this is the first study in marine teleost investigating the nutritional regulation of ch25h expression.